IDENTIFIKASI PEMANFAATAN ARKADE DAN IMPLEMENTASI GSB NOL DI JAKARTA BARAT - Theresia Budi Jayanti; Irene Syona Darmady; Danang Priatmodjo (ATRIUM: Jurnal Arsitektur, 2020)
Title: Identification of Arcade Utilization and Implementation of Zero Setbacks in West Jakarta Perda No. 1 - 2014 about Jakarta’s Zoning Regulation mentioned about guidance which control building setback, streets, and right of way; in the way to achieve well-ordered cityscape in terms of urban design and architecture. However, there are unclear statement about area characterized with arcade and zero setbacks. In actual condition, there is location dominated by zero setbacks appearance based on necessary needs. This issue trigerred visual cluttering in cityscape. Based on that condition, this study tried to understand and identify location in administrative West Jakarta area which indicate arcade and zero setbacks due to its affected aspects. Site observation and mapping used as a method to finding data and analyze the process to get overall trend and tendency. Findings about this study represent such condition wtih incontinuity pattern about arcade and zero setbacks in some area or corridor. Proposal about spatial planning in conclusion of this study role as suggestion to evaluate the regulation.